The Role of Occupational Safety and Health in Improving Employee Performance - Nenosaban, Briliani; Gana, Frans; Maku, Grace Martini (Journal of Tourism Economics and Policy, 2026)
This study examines the role of occupational safety and occupational health in improving employee performance at CV. Auto Nusa Abadi Kupang. The research uses a quantitative approach with a survey method, involving 68 employees as respondents. Occupational safety and occupational health serve as the independent variables, while employee performance acts as the dependent variable. Data were analyzed using descriptive statistics and multiple linear regression to determine both partial and simultaneous effects. The results show that occupational safety significantly affects employee performance, and occupational health also has a significant effect. Simultaneously, both variables contribute to improving performance indicators, including work quality, productivity, responsibility, teamwork, and initiative. The study highlights the importance of implementing occupational safety and health programs as strategic efforts to enhance performance and create a secure, healthy, and productive work environment.